Front Cover: Bottom‐Up Synthetic Biology: Towards the Modular Design of Artifical Cells from Functional Modules (Adv. Biosys. 6/2019). Issue 6 (13th June 2019) - Landfester, Katharina; Sundmacher, Kai
Abstract : This special issue on synthetic cells features a compilation of 12 articles dedicated to different facets of bottom‐up synthetic biology. Minimization is an important strategy in synthetic biology, which can be achieved best by stepwise modular assembly of a living system using well‐defined functional parts. This is the concept of bottom‐up synthetic biology. Starting from single molecular bricks, functional parts and modules can be assembled and used to synthesize an artificial cell or even an artificial organ.